Draft Annual Plan 1995-96 Maharashtra State Part I - Planning Commission (Planning Commission, 1995)
The priorities as determined by the National Development Council (NDC) in June 1991 for the Eighth Five Year Plan have reflected in the earlier three annual plans of the State. Annual Plan 1995-96 is the fourth year of the Eighth Five Year Plan. the priorities as determined by the National Development Council for the Eighth Five Year Plan, shall continue to have sufficient outlays in the Annual Plan 1995-96. Hence, employment generation, containment of population growth, universalisation of elementary education, eradication of illiteracy, providing safe drinking water, health care, self sufficiency in agriculture, strengthening of infrastructure i.e. Energy, Transport, Communication and Irrigation, effective decentralisation and encouragement of local initiatives, adequate funding of on-going projects and timely implementation of Externally Aided Projects will be the thrust areas of the Annual Plan 1995-96.
Planning Department, Government of Maharashtra